2018
DOI: 10.3329/bjme.v9i2.38996
|View full text |Cite
|
Sign up to set email alerts
|

Stressors Perceived by the Para-clinical Undergraduate Medical Students

Abstract: Medical curricula are considered as toughest of all curricula of undergraduate professionals. Student faces many stress provoking factors in the academic course. In time identification and adoption of coping strategy can ensure proper achievement of goal of the curriculum. The objective of this prospective study was to find out the nature and intensity of stressors perceived by the mid level medical students (phase II & III) before their summative examination. Regularly passed students of phase II and III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A study was conducted at the University Hospital of Tuebingen, Germany on 1,425 participants, 2018 showed various stressors challenging the medical students through their academic study as private related stressors (financial worries, side job, living situation, and conflicts with parents) and training related stressors (missing consultation and support, bad time management, and lack of enough training time). 22 On contrary a study done in Bangladesh 23 on undergraduate medical students showed that the Intensity of stressors was significantly higher in preclinical students than clinical ones (p=0.000), and revealed many stressors affect them as getting low marks and facing parental expectations, facing a personal illness or death of patients, too much restriction in campus, high workload and crowded curriculum, and inadequate medical skill practice. Another study conducted on 68 medical students in Germany to assess Medical students' perceptions of stress due to academic studies and its interrelationships with other domains of life showed that starting medical studies are linked with significant personal challenges that may develop over stress and burnout syndrome and affect the scholar achievement, such as living alone for the first time, a little time for rest and physical activities and a healthy lifestyle, Feelings of social isolation especially during exam stages, Side jobs were perceived to increase stress by time and effort consumption, and high surrounding expectations.…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted at the University Hospital of Tuebingen, Germany on 1,425 participants, 2018 showed various stressors challenging the medical students through their academic study as private related stressors (financial worries, side job, living situation, and conflicts with parents) and training related stressors (missing consultation and support, bad time management, and lack of enough training time). 22 On contrary a study done in Bangladesh 23 on undergraduate medical students showed that the Intensity of stressors was significantly higher in preclinical students than clinical ones (p=0.000), and revealed many stressors affect them as getting low marks and facing parental expectations, facing a personal illness or death of patients, too much restriction in campus, high workload and crowded curriculum, and inadequate medical skill practice. Another study conducted on 68 medical students in Germany to assess Medical students' perceptions of stress due to academic studies and its interrelationships with other domains of life showed that starting medical studies are linked with significant personal challenges that may develop over stress and burnout syndrome and affect the scholar achievement, such as living alone for the first time, a little time for rest and physical activities and a healthy lifestyle, Feelings of social isolation especially during exam stages, Side jobs were perceived to increase stress by time and effort consumption, and high surrounding expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al (2018) described the stressors facing medical students in the millennial generation: medical school workload, performance pressure, financial problems, time constraints, and lack of balance [ 21 ]. Several other American [ 22 , 23 ], European [ 24 , 25 ], and Asian [ 26 28 ] studies have also noted these as stressors among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time Balint groups can help physicians cope with burdensome experiences [ 19 ]. Likewise, medical students can be confronted with difficult situations like the sudden death of a patient [ 20 ]. Only few studies have investigated the usefulness of Balint groups for medical students.…”
Section: Introductionmentioning
confidence: 99%